Egy attitűdvizsgálat eredményei a magyar és lengyel rejtett gazdaságról = Results of an attitude survey on Hungarian and Polish hidden economy - Benke, Gréta; Karcagi-Kováts, Andrea (Közép-Európai Közlemények, 2018)
The fight against shadow economy and the reduction of its size and spread are important economic policy objectives today. The struggle against it is difficult not merely because the phenomenon is intentionally or unintentionally hidden from the authorities and agencies, but similarly, although a significant part of our society does not consider these hidden activities as acceptable examples to follow, in their mindset this is a potential and venial form of behaviour. In our research, we investigated Polish and Hungarian people’s opinion about the hidden economy. Our aim was to stay within the confines of an attitude study to shed light on what people’s general attitude to the hidden economy was, whether they knew its definition and the activities included and whether they were aware of their social and economic impact. To achieve our goal, we carried out a survey among Polish and Hungarian people. Our research analysed and compared the responses of 803 Polish and 2055 Hungarian people, furthermore, we created a composite indicator. In this indicator, we took account of the values of responses to those questions which measured the attitude of the respondents to the hidden economy. Based on the results it can be concluded that a large part of the Polish and Hungarian people knows about most of the hidden activities, but the judgement of the phenomenon is quite different for each individual and shows uncertainty in both countries. The responses – regardless of nationality – reveal that human intentions and reality are dissimilar. This means that although the respondents consider it important to follow the rules and comply with the law, they are often participants of the black economy through their different activities.